2020
DOI: 10.3390/ijms21114056
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type- and Sex-Specific Dysregulation of Thyroid Hormone Receptors in Placentas in Gestational Diabetes Mellitus

Abstract: Thyroid hormones are essential for development of trophoblasts and the fetus. They also regulate a wide range of metabolic processes. We investigated the influence of maternal gestational diabetes mellitus (GDM) on thyroid hormone receptor (THR) isoforms THRα1, THRα2, THRβ1 and THRβ2 of the human placenta in a sex- and cell-type specific manner. Term placental tissue was obtained from women with (n = 40) or without GDM (control; n = 40). THRs levels were measured by semi-quantitative immunohistochemistry and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…A previous study reported that maternal GDM exerts effect on the human placental thyroid hormone receptor (THR) subtypes THRα1, THRα2, THRβ1, and THRβ2. 22 We speculate that this effect may be persistent if a woman with GDM became pregnant again. The association between thyroid autoimmunity and spontaneous type 1 diabetes has been well established by numerous studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A previous study reported that maternal GDM exerts effect on the human placental thyroid hormone receptor (THR) subtypes THRα1, THRα2, THRβ1, and THRβ2. 22 We speculate that this effect may be persistent if a woman with GDM became pregnant again. The association between thyroid autoimmunity and spontaneous type 1 diabetes has been well established by numerous studies.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, the incidences of thyroid disorders and thyroiditis were higher in subsequent pregnancies ( p = .003 and p = .005). A previous study reported that maternal GDM exerts effect on the human placental thyroid hormone receptor (THR) subtypes THRα1, THRα2, THRβ1, and THRβ2 22 . We speculate that this effect may be persistent if a woman with GDM became pregnant again.…”
Section: Discussionmentioning
confidence: 89%
“…Genes in the subnetwork were enriched in certain hormone signaling pathways, including thyroid hormone and oxytocin (OT). Recent evidence indicates that perturbations of the thyroid hormone signaling pathway and antibodies are associated with GDM development and mal-outcome [ 49 , 51 ]. Emerging evidence suggests a role of OT in the pathogenesis of insulin resistance, obesity, and dyslipidemia [ 52 , 53 ], which are hallmarks or risk factors for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that a small but significant population of patients with GDM develop postpartum T1DM (52,53). Emerging evidence suggests that perturbations of the thyroid hormone signaling pathway and antibodies are associated with GDM development and adverse outcomes (54,55). In terms of the GO biological process category, the DMRGs were closely related to inflammatory-and immune-related biological processes.…”
Section: Discussionmentioning
confidence: 99%